Experimental testing and validation of the dynamic model of a magneto-solid damper for vibration control. (1st March 2022) - Amjadian, Mohsen; Agrawal, Anil K.; Silva, Christian E.; Dyke, Shirley J.
Highlights: A new damper named as magneto-solid damper (MSD) is proposed for vibration control. The MSD shows smooth and large hysteretic loops by combining friction and eddy current damping. A proof-of-the-concept prototype of the MSD is designed by finite element and analytical models. The prototype is fabricated and tested in laboratory to validate its dynamic model. Abstract: This paper focuses on characterization testing and validation of the dynamic model of a new type of high-damping density electromagnetic-based damping device (EMD) referred to as Magneto-Solid Damper (MSD) in which an eddy current damping mechanism acts in parallel with a solid friction mechanism to dissipate the input kinetic energy. The proposed MSD consists of a ferromagnetic plate, two copper plates placed on two sides of the ferromagnetic plate in parallel, and a planar array of permanent magnets (PMs) placed between the ferromagnetic plate and each of the two copper plates. The PMs arrays are attached to the ferromagnetic plate through non-magnetic friction pads. The friction force is developed between these friction pads and the ferromagnetic plate when the PMs arrays move relative to the ferromagnetic plate. The motion of the PMs arrays relative to the copper plates, on the other hand, generates the eddy current damping. A laboratory prototype of the proposed MSD has been designed and fabricated for the purpose of characterization testing. Finite element and simplified analytical models of this damper have also been developed to analyze the magnetic interaction between the PMs arrays and the ferromagnetic and copper plates. A dynamic model has been developed to characterize the force–displacement behavior of the proposed MSD. The parameters of this dynamic model are identified through a series of characterization tests on the prototype MSD under harmonic excitations of different frequencies. The identified dynamic model is validated by subjecting the prototype MSD to real ground motion records. It is concluded that that the proposed dynamic model is capable of describing the force–displacement behavior of the proposed MSD for a wide range of operating conditions.